2015
DOI: 10.1039/c5dt01648g
|View full text |Cite
|
Sign up to set email alerts
|

Five water-soluble zwitterionic copper(ii)-carboxylate polymers: role of dipyridyl coligands in enhancing the DNA-binding, cleaving and anticancer activities

Abstract: Five water-soluble zwitterionic copper-carboxylate polymers were prepared from the reaction of N-carboxymethyl-(3,5-dicarboxyl)pyridinium bromide (H3CmdcpBr) with Cu(NO3)2 in the presence of NaOH by modulating the temperature, solvent and ancillary dipyridyl ligands. These complexes include a 1D ladder-shaped polymer {[Cu3(Cmdcp)2(OH)2(H2O)2]·H2O}n () formed in H2O at room temperature, and a 2D network polymer {[Cu(Cmdcp) (H2O)2]·2H2O}n () isolated in H2O at 135 °C. At 100 °C in H2O/DMF, the same reaction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The cleavage efficiency of 4b was kept unaffected in the presence of hydroxyl radical scavengers DMSO and MeOH (lane 3 and lane 4) and a singlet oxygen scavenger NaN 3 (lane 5) (Figure F), which means that HO • and/or 1 O 2 were not involved in the DNA cleavage. When a DNA mimicing phosphate, bis­(2,4-dinitrophenyl) phosphate (BDNPP), was added (lane 6), the reaction of DNA cleavage was partially inhibited, suggesting that the hydrolysis pathway for the DNA cleavage process is possible . Notably, when a hydrogen peroxide scavenger KI (lane 7) was added, the DNA cleavage was significantly inhibited, implying that H 2 O 2 was the reactive species in the cleavage process. ,, Furthermore, EDTA (lane 8) efficiently inhibited DNA cleavage, implying that the complexation of the 4a ligand with Cu 2+ is crucial to the cleavage. Taken together, these results implied the compound bound to DNA by the moderate intercalative binding mode, and efficiently cleaved pBR322 DNA probably via an oxidative mechanism with the involvement of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cleavage efficiency of 4b was kept unaffected in the presence of hydroxyl radical scavengers DMSO and MeOH (lane 3 and lane 4) and a singlet oxygen scavenger NaN 3 (lane 5) (Figure F), which means that HO • and/or 1 O 2 were not involved in the DNA cleavage. When a DNA mimicing phosphate, bis­(2,4-dinitrophenyl) phosphate (BDNPP), was added (lane 6), the reaction of DNA cleavage was partially inhibited, suggesting that the hydrolysis pathway for the DNA cleavage process is possible . Notably, when a hydrogen peroxide scavenger KI (lane 7) was added, the DNA cleavage was significantly inhibited, implying that H 2 O 2 was the reactive species in the cleavage process. ,, Furthermore, EDTA (lane 8) efficiently inhibited DNA cleavage, implying that the complexation of the 4a ligand with Cu 2+ is crucial to the cleavage. Taken together, these results implied the compound bound to DNA by the moderate intercalative binding mode, and efficiently cleaved pBR322 DNA probably via an oxidative mechanism with the involvement of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the Cu compound derived from thiosemicarbazone shows promise for development as a multitarget anticancer metal lead drug. Excitingly, many studies revealed that 64 Cu 2+ can be used as a cost-effective probe for positron emission tomography (PET) imaging of various types of cancers. 77−80 It suggested that we can design a multifunction 64 Cu 2+ compound derived from thiosemicarbazide that simultaneously diagnoses and treats cancer.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the formation of CPs, molecular self‐assembly of metal ions and organic ligands, especially polycarboxylate ligands based on the principle of crystal engineering has proved to be an efficient approach . Using various coordination tendencies of metal ions, multidentate organic ligands and mixed ligands are helpful in the construction of a diverse topology of architectures . Furthermore, carboxylate groups in these ligands are efficient for the generation of diverse structures and topologies due to their polytropic linking modes, when they are deprotonated .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, some Cu(II) complexes have been reported to serve as potential anticancer and cancer‐inhibiting agents, and several of them have been found to be active both in vitro and in vivo . For instance, various chemical nucleases containing Cu(II) were reported to be cytotoxic against tumoral cells and triggered cellular apoptosis in vitro . Recently, Ma et al reported three ternary Cu(II) complexes with amino acid chains and heterocyclic bases, which could cause DNA damage and had significant cytotoxic activity against human tumor cells .…”
Section: Introductionmentioning
confidence: 99%